Physical and physiological factors associated eith success in professional alpine skiing - Neumayr, G.; Hoertnagl, H.; Pfister, R.; Koller, A.; Eibl, G.; Raas, E. (International Journal of Sports Medicine, 2003)
Scientific data on the physiological profile of world class skiers are sparse. During the last decade the Austria Ski Team was the most successful in the world. It was the objective of this study to describe the physical and physiological characteristics of World Cup (WC) skiers. Twenty female and 28 male members of the Austrian WC Ski Team were examined pre- and post-seasonally from 1997 to 2000. Physical parameters such as age, height, body mass, body mass index, percent body fat and thigh circumference were recorded from each athlete. The physiological variables investigated consisted in the aerobic power and in the muscle strength of the lower limbs. Racing performance was defined by the WC ranking position. The athlete's aerobic performance capacity was assessed by maximal exercise testing on a bicycle ergometer, and the isokinetic muscle strength of the knee extensor and flexor muscles by the use of a computer-interfaced dynamometer. From 1997 to 2000 about half (48 %; n = 106) of all alpine WC racing events (n = 221) were won by the athletes investigated. The typical world class skier is in the mid-twenties (25.2 y [ female symbol ]; 27.6 y [ male symbol ]). The mean values for height were 1.66 m ( female symbol ) vs. 1.81 m ( male symbol ), for body mass 65.1 kg (f) vs. 87 kg ( male symbol ) and for the percentage of body fat 24.5 % ( female symbol ) vs. 15.8 % ( male symbol ). The maximum power output was 4.3 +/- 0.4 ( female symbol ) and 4.7 +/- 0.4 W/kg ( male symbol ), the corresponding values for V.O (2)max were 55 +/- 3.5 ( female symbol ) and 60 +/- 4.7 ml/kg/min ( male symbol ). The maximal values for peak torque and work for knee extension amounted to 206 +/- 21 ( female symbol ) and 334 +/- 43 Nm ( male symbol ), and 2690 +/- 364 ( female symbol ) and 4414 +/- 629 J ( male symbol ), respectively. In both sexes there were neither significant laterality nor dysbalance. The hamstring/quadriceps ratios were between 0.57 - 0.60. Among all physical and physiological variables, only the aerobic power in males was found to be strongly correlated (r = 0.947; p = 0.001 for W (max); r = 0.964; p < 0.001 for V.O (2)max) to racing performance. The study proves the practical experience that success in professional alpine skiing is not related to single physiological variables. Two main factors, however, are crucial, i. e. high levels of aerobic power and muscle strength.